Hormonalna terapia zastępcza – czy droga podania ma znaczenie? - Tkaczuk-Włach, Joanna; Sobstyl, Małgorzata; Włach, Rafał; Jakiel, Grzegorz (Menopause Review/Przegląd Menopauzalny, 2013)
The past decade has seen dramatic change in opinions of the menopausal hormonal therapy (MHT). After the re-analysis of the WHI (Women’s Health Initiative) results it becomes clear that the risk and benefits of MHT differ for women during the menopause transition compared to those for older women. This paper focused on the benefits of the transdermal route of hormone administration.